Evaluation of the Psychometric Properties of a Newly Developed Chinese Screening Tool for Speech Disorders in Patients With Parkinson's Disease. Issue 2 (June 2023) - Chen, Chi-Lin; Lin, Ching-Huang; Su, Chen-San; Cheng, Hsiang-Chun; Chen, Li-Mei; Cherng, Rong-Ju
The study aimed to analyze the psychometric properties of a newly developed Chinese screening tool, the Chinese Version of the Speech Disorders in Parkinson's Disease Questionnaire (SDPD-C). The SDPD-C contains a 24-item questionnaire with four assessment domains. Overall, 93 patients with idiopathic Parkinson's disease (PD) (age 70.1 ± 8.9 years) and 76 healthy older adults (age 67.2 ± 8.1 years) participated in the psychometric analysis study. The internal consistency of the SDPD-C was .91 (four dimensions: .69–.85), and test-retest reliability was .91 (four dimensions: .85–.88). The SDPD-C was highly correlated with the Voice Handicap Index-10 and Movement Disorder Society-Unified Parkinson's Disease Rating Scale II 2.1 (r = .83 and .78, respectively). The SDPD-C scores also differed significantly between stages 1 and 4 of the Hoehn and Yahr Scale ( p < .05). The area under the receiver operating characteristic curve was .955 (95% confidence interval, .927–.983; asymptotic significance p < .001), and the optimal cut-off score of this study was 36, with a sensitivity of .849 and specificity of .947. The results indicate that SDPD-C showed good reliability, validity, accuracy, and discrimination. It can be used as a screening tool for speech disorders in patients with PD.